Treatment of Hepatitis C Disease with Standard Therapy and its Correlation with Specific Genotype of Interleukin - Hepatitis C, polymorphism, Interferon (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the association of interleukin-28b- RS12980275 with response to treatment with interferon α-2b & ribavirin in chronic hepatitis c patients Methodology: A case control study was designed that includes219 HCV patients treated with INF and Ribavirin. Out of 219, 95 were males while 124 were females. They are classified into two groups. Those achieved sustained virological response (SVR) and those who did not sustained virological response (Non-SVR). All the demographics and biochemical data were recorded on a Performa that includes age, ALT and viral load. The data were analyzed using SPSS version 16.0. Results: Patients having IL28B-rs12980275 AG genotypes respond better to interferon and ribavirin treatment (p-value=0.01, OR=2.91). Furthermore, HWE was also calculated for both groups in which the responders do not corresponds to HWE (p-value= <0.001) while the non-responders were found to be consistent with HWE (p-value= 0.31). Conclusion: Polymorphism in IL28B (rs12980275) was found to be significantly associated (p-value = 0.009) with the treatment outcome in patient with hepatitis C receiving standard therapy regimen (Interferon + Ribavirin).